Jesus according to Ibn al-’Arabī and Christian scholars - Yoo, Jeong Jae (AUC Knowledge Fountain, 2013)
Despite the differences between Islam and Christianity, Islam is the only non-Christian religion in the world, which requires its adherents to believe that Jesus is one of the prophets of God. Ibn al-’Arabī, one of the Sufi mystics of the 12th century, wrote an entire chapter devoted to Jesus in his book, Fuṣūṣ al-ḥikam, translated as the Bezels (or Seals) of Wisdom. In this chapter, Jesus is characterized by five names that most clearly explain his attributes. These names are ‘the Spirit of God’, ‘the Word of God’, ‘the Breath of God’, ‘the Mercy of God’, and ‘the Slave of God’. Each of these names represents an important characteristic that Ibn al-’Arabī wishes to convey about Jesus as the Seal of the general Sainthood, his most famous notion manifested in all of Ibn al-’Arabī’s writings. Christian scholars such as Thomas Aquinas, St Anselm of Canterbury and Meister Eckhart – who lived during the same period - wrote a considerable amount on Christian doctrines. These writers discussed crucial topics such as the Trinity, the virgin birth, the Judgment day, the angels, and more. This thesis is a comparative study of Jesus as portrayed by Ibn al-’Arabī and the three Christian scholars: analyzing and comparing the embedded meanings of the five names mentioned above. It can be concluded that all of the differences between Ibn al-’Arabī and Christian scholars derived from fundamentally divergent perspectives on the deity of Jesus Christ. Although there are some superficial similarities, there is not any significant similarity between the two sides.